Relaxed design conditions using Takagi-Sugeno fuzzy models and Lyapunov-Floquet transformation for controlling time-varying periodic systems - Travassos, Marco A [UNESP]; Cardim, Rodrigo [UNESP]; Teixeira, Marcelo CM [UNESP]; Assunção, Edvaldo [UNESP] (SAGE Publications, 2022)
This manuscript approaches the Takagi-Sugeno fuzzy control technique, the Lyapunov-Floquet transformation, and their applications for controlling linear time-varying systems. Each of the techniques is applied in the control of a linear time-varying periodic system in order to compare their effectiveness. A hybrid control method involving the Takagi-Sugeno fuzzy control and the Lyapunov-Floquet transformation is proposed. In this method, the stability of the closed-loop system is mathematically guaranteed. In addition, this new procedure can reduce the conservatism of time-varying periodic systems with uncertainties in the input matrix. Finally, an application of the hybrid method is presented in a time-varying periodic system considering a constraint on input and uncertainties on the input matrix.
Keywords: fuzzy control; linear matrix inequalities; Lyapunov-Floquet transformation; parallel distributed compensation; time-varying periodic system